Sportorthopädie - Schaffran P; Altfeld S; Kellmann M; 2 (Dynamic Media Sales Verlag, 2016)
This review article summarizes the current state of burnout research, factors contributing to burnout, diagnostic instruments, and approaches for interventions. Coaches have to deal with emotional and physical stress that can influence their wellbeing and in turn, potentially impact athlete performance. Stressors include conflicts, pressure and expectations, managing the competition environments, athlete concerns, coaching responsibilities to the athletes, consequences of sport status, competition preparations, organizational management, sacrificing personal time, and isolation. A uniform definitionof burnout does not exist. Research in the field of sport and especially coaches has mainly focused on the widely accepted concept of burnout by Maslach und Jackson. They identified key symptoms, which included emotional exhaustion, depersonalization, and reduced personal accomplishment.Studies on factors influencing burnout show contradictory results. Overall, demographic variables (e.g., age and gender) seem to have minor effects on burnout, whereas coaches perception and appraisal of social and management support might play an important role. Furthermore, personality (e.g., perfectionism), motivation and the behavior of a coach influences the individual assessments of stressful situations.Especially within the last years, burnout research outsideofthe sport context has produced numerous findings regarding contributing factors and intervention strategies. These findings should be transferred to the coaching environment.KEY WORDS: Burnout, Coaches, Stressors, Emotional Exhaustion